2016
DOI: 10.3389/fpsyt.2016.00193
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Attentional Control in Pedophiles in a Sexual Distractor Task

Abstract: Pedophilic disorder, a subtype of paraphilia, is defined as a recurrent sexual interest in prepubescent children, which is characterized by persistent thoughts, fantasies, urges, sexual arousal, or behavior. Besides a deviant sexual preference, sexual preoccupation was found to be a dynamic risk factor for reoffending. Thus, it is conceivable that sex offenders and especially sex offenders against children have difficulties to control their responses to sexual stimuli. In the current study pedophiles, forensic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…As discussed in Structural and Functional Imaging, a diminished fronto-limbic functional connectivity could be seen as a neurobiological correlate for an (generally) impaired ability to exert inhibitory control over behavior, which seems to be associated with child sexual offending. Furthermore, pedophilic CSOs also seem to have lower attentional control capacities than non-pedophilic controls, as was shown in a sexual distractor task with high discrimination accuary while measuring eye movements (120). Finally, the application of virtual reality approaches could be promising to examine a more realistic, inhibitory control behavior; for instance when confronting participants with children in a virtual supermarket (138).…”
Section: Potential Biomarkers For Therapy Response and Risk Assessmentmentioning
confidence: 97%
See 2 more Smart Citations
“…As discussed in Structural and Functional Imaging, a diminished fronto-limbic functional connectivity could be seen as a neurobiological correlate for an (generally) impaired ability to exert inhibitory control over behavior, which seems to be associated with child sexual offending. Furthermore, pedophilic CSOs also seem to have lower attentional control capacities than non-pedophilic controls, as was shown in a sexual distractor task with high discrimination accuary while measuring eye movements (120). Finally, the application of virtual reality approaches could be promising to examine a more realistic, inhibitory control behavior; for instance when confronting participants with children in a virtual supermarket (138).…”
Section: Potential Biomarkers For Therapy Response and Risk Assessmentmentioning
confidence: 97%
“…In another experimental setting, a sexual distractor task, the same subjects had to solve a cognitive task while simultaneously being presented with an image of a sexual stimulus [child or adult stimulus (120)]. Hence, this task requires attentional control in the presence of sexual stimuli.…”
Section: Eye Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…The task takes advantage of the effect that sexually attractive imagery induces a sexual content-related delay to subsequent cognitive processes (Dombert et al, 2017;Geer & Bellard, 1996;Gress & Laws, 2009;Mokros et al, 2010). The relative preference for certain kinds of sexual stimuli is estimated by measuring the time it takes a participant to release attention from the image to perform the primary target detection task (for a different example of attention-based indirect tests, see Jordan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been further suggested that this attention bias might be associated with impaired cognitive control over sexual responses (Jordan et al, 2016). In support of this, decreased activity in frontal regions such as the left dorsolateral prefrontal cortex (dlPFC) has been found in sex offenders with child victims (SOC) with PD compared to healthy controls, in response to sexual images (Mohnke et al, 2014;Poeppl et al, 2013;Walter et al, 2007).…”
mentioning
confidence: 97%